IMPLEMENTASI PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN PADA MASA PANDEMI COVID-19 - Warkintin Warkintin; Muhammad Rian Subekti; Hendrikus Hendrikus (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2022)
The general objectives of this study are to describe the implementation of PJOK learning for class IV B at SDN 1 Kenukut during the COVID-19 pandemic, to find out the Inhibiting and Supporting Factors in the PJOK learning process for class IV B at SDN 1 Kenukut during the COVID-19 pandemic, PJOK learning outcomes during the COVID-19 pandemic. The method used in this study is a qualitative method with a descriptive research form, while the subjects in this study are homeroom teachers, PJOK teachers who collect 2 people and class IV B students who return 25 people. The method used in this study is a purposive method. The sampling object is students in the PJOK learning process and class IV B teachers at SDN 1 Kenukut. Data collection techniques used are Non-Participant Observation Techniques, Semi-Structured Interview Techniques, and Documentation Techniques. While the data collection tools are Observation sheets, Interview sheets and Documentation sheets in the form of Absence, RPP, Assignments, and Student Learning Outcomes. Results Based on research at SDN 1 Kenukut, during the COVID-19 pandemic in the 2020/2021 school year, the learning process at SDN 1 Kenukut uses online and offline learning processes, online learning in question is learning using the whatsapp application where the teacher informs students to take assignments go to school and if you don't understand then you can ask the teacher via whatsapp, while offline learning is where students do assignments from home. As for the instrument in the teacher's assessment of student results, namely, the accuracy of student answers, timeliness and timeliness given.